Dehydration of cellulose to levoglucosenone using polar aprotic solvents. Issue 6 (3rd June 2015) - Cao, Fei; Schwartz, Thomas J.; McClelland, Daniel J.; Krishna, Siddarth H.; Dumesic, James A.; Huber, George W.
<x xml:space="preserve">Abstract</x> Herein, we report an approach to produce levoglucosenone (LGO) from cellulose in yields up to 51% under mild reaction conditions (170–230 °C; 5–20 mM H2SO4) using polar, aprotic solvents such as tetrahydrofuran (THF).